The Use of Pupillometry in Autobiographical Implicit Association Test - Ogawa, Tokihiro; Todoriki, Natsu; Tsuneoka, Michiko (Frontiers in Psychology, 2021)
The Autobiographical Implicit Association Test (aIAT) is a reaction time-based methodology to assess one’s recognition of the truth value of propositions about an autobiographical episode. This study introduced pupillometry to examine its utility as an additional measure of aIAT. Participants blindly chose one of two cards and memorized it. They then underwent the aIAT to assess the cards they chose. The pupil diameter was larger in the block in which sentences related to the chosen card shared the same response key with sentences describing false events than the block in which sentences related to the chosen card shared the same response key with true-event sentences. Although preliminary, pupil measurement also yielded high efficiency in discriminating the chosen card. These results indicate that pupillometry can be used as a measure of aIAT.